ANALISA PENGARUH KINERJA KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN TERJADINYA FINANCIAL STATEMENT FRAUD - Ardhiansyah, Arief Satria; Kusuma, Hadri; Sa’dani, Olivi Sabilla (Universitas Ahmad Dahlan, 2019)
The objective of this research to analyze factors that have impact to financial statement fraud. Independent factors used in this research consists of financial distress, liquidity, leverage, and corporate governance. In other hand, the objective of this research also to analyze the factors that have influence to financial distress. Independent factors used in this research consist of profitability, liquidity, leverage, and corporate governance. Samples is all of manufacturing companies that listed in Indonesian Stock Exchange (BEI) period 2011-2015. Sampling method using purposive sampling with criterias setted by researcher and got 634 companies as the samples. Method of data analysis using path analysis and use PLS as software assisted. The results of this research are financial distress, liquidity, leverage, and corporate governance have a significant influence to financial statement fraud. In other hand profitability, liquidity, leverage, and corporate governance have significant influence to the financial distress.